Hiroshima‒Nagasaki Remembered Through the Body: Haptic visuality and the skin of the photograph. (2nd January 2018) - Matheson, Neil
Abstract : The continued growth in the interaction of photography with other media, together with a revived interest in analogue technologies in reaction against the growing digitisation of the image, have served to focus interest in the broader sensorial experience of the photograph. Film theory, using a range of ideas drawn from phenomenology and embodiment theory, provides a useful model through which to rethink our understanding of the way in which photographs are experienced at the level of the body. Working critically with a range of such ideas, this paper takes the example of photographs of the nuclear bombings of Hiroshima and Nagasaki, together with subsequent photographic projects based on those events, in order to further contribute to this rethinking of the sensorial experience of the photograph.